Posttraumatic Stress Disorder, Orientation to Pain, and Pain Perception in Ex-Prisoners of War Who Underwent Torture. Issue 6 (July 2017) - Tsur, Noga; Defrin, Ruth; Ginzburg, Karni
ABSTRACT: Objective: Studies suggest that torture survivors often experience long-term chronic pain and increased pain perception. However, it is unclear whether the actual experience of torture or rather the subsequent posttraumatic stress disorder (PTSD) explains these pain problems. Furthermore, although catastrophic and fearful orientations to pain have been suggested to play a significant role in the association between trauma and pain, the underlying mechanisms remain unclear. This study examined whether chronic pain and pain perception among torture survivors are associated with torture experience or PTSD and whether catastrophic and fearful orientations mediate or moderate these associations. Methods: Fifty-nine ex-prisoners of war who underwent torture and 44 matched veterans participated in this study. Pain perception was evaluated by assessing pain threshold and reactivity to experimental suprathreshold noxious stimuli. Participants completed self-administered questionnaires assessing PTSD, chronic pain, pain catastrophizing, and fear of pain. Results: Although chronic pain was associated with PTSD (0.44 < β < 0.49, p < .002), increased pain perception was correlated with torture (0.33 < β < 0.65, p < .05). Pain catastrophizing was found to mediate the association between PTSD and chronic pain (β = 0.18 and 0.19, respectively; p < .05). Fear of pain moderated the association between torture and pain perception (β = 0.41 and 0.42, respectively; p < .017). Conclusions: The findings suggest that chronic pain is contingent upon the psychological toll of torture, that is, PTSD. This study also indicates that PTSD exacerbates catastrophic orientation, which in turn may amplify chronic pain. Reactivity to experimental noxious stimuli was related to previous experiences of torture, which enhances perceived pain intensity when interacting with a fearful pain orientation. These findings highlight the significance of orientation to bodily experiences after trauma.